Major and trace element data of volcanic glass shards from ash beds drilled at ODP Site 882; trace element and Pb-Nd isotope analyses of separated fresh volcanic particles from ODP Site 882 ash beds ... - Straub, Susanne; Reilly, Brendan; Raymo, Maureen; Gómez-Tuena , Arturo; Wang, Kuo-Lung; Widom, Elisabeth; Kuentz, David; Arculus, Richard (Interdisciplinary Earth Data Alliance (IEDA), 2024)
This dataset presents major and trace elements of single volcanic glass shards, and trace element and Pb-Nd isotope analysis from volcanic ash particles from ODP Site 822. Volcanic glasses were analyzed by EMPA at American Museum of Natural History and by laser-ablation ICP-MS at the Institute of Earth Sciences, Academia Sinica in Taipei (Taiwan). Trace element data were obtained by solution ICP-MS at the UNAM Centro de Geociencias (CGEO) in Queretaro (Mexico). The chemical separation for Pb and Nd was done at the UNAM Centro de Geociencias (CGEO) in Queretaro (Mexico), whereas the Pb and Nd isotope analyses were performed by MC-ICPMS at Miami University in Oxford (Ohio). ... : Straub, S.M., Reilly, B.T., Raymo, M.E., Gomez Tuena, A., Wang, K.L., Widom, E., Kuentz, D., Arculus, R.J., 2024. Patterns of Plio-Pleistocene Ice Volume Variability Recorded by the Large-Magnitude Explosive Eruptions from the Kamchatka-Kurile Volcanic Arc. Geochem Geophys Geosys. ...